(18)F-Positron Emitting/Trimethine Cyanine-Fluorescent Contrast for Image-Guided Prostate Cancer Management - Kommidi, Harikrishna (J Med Chem, 2018)
[Image: see text] [(18/19)F]-4, an anionic GCPII/PSMA inhibitor for image-guided intervention in prostate cancer, is described. [(19)F]-4 is radiolabeled with a radiochemical yield that is ≥27% and a molar activity of 190 ± 50 mCi/μmol in a <1 h, one-step, aqueous isotopic exchange reaction. [(19)F]-4 allows PSMA expression to be imaged by fluorescence (FL) and [(18)F]-PET. PC3-PIP (PSMA-positive, EC(50) = 6.74 ± 1.33 nM) cancers are specifically delineated in mice that bear 3 million (18 mg) PC3-PIP and PC3 (control, PSMA-negative) cells. Colocalization of [(18/19)F]-4 PET, fluorescence, scintillated biodistribution, and PSMA expression are observed.